Gregory Research Beliefs Scale: Psychometric properties and social work student survey results. - Gregory Jr., Virgil L. (Social Work Education, 2022)
In the United States (US) there is an increasing numbers of social work students and social work practitioners represent the majority of mental health professionals. Consequently the role of evidence-based social work practice (EBSWP) in education becomes more important. Past research supported the psychometric properties of the Research Beliefs Scale (GRBS) with social work students. The purposes of the present study are two-fold. The first purpose is to evaluate the factor structure and internal consistency reliability of the GRBS in a distinct sample of US MSW and BSW students. The second purpose is to evaluate the extent to which the US MSW and BSW students believe that research has value for social work practice. Data collection consisted of face-to-face and online formats. Factorial validity was examined using a principal component analysis. Internal consistency reliability was measure via Cronbach's alpha. The data provided empirical evidence for the one-factor GRBS model and demonstrated high internal consistency with a Cronbach's alpha of.95. The data cautiously showed support for US social work students' beliefs in the value or research for social work practice. Applications of the RBS to social work education and future research are discussed.